Conflict of the Main Character in the Movie “Purple Hearts” - Ni Putu Regina Pradnyamitha; Ni Made Verayanti Utami (Austronesian: Journal of Language Science & Literature, 2024)
This study aims to dissect the fundamental person’s contention, examine the primary person’s outer struggle, and recognize how the principal character beats the contention in Elizabeth Allen’s film. The data for this study consists of the dialogue and interactions involving Cassie, a character in the film Purple Hearts. The data will be analyzed qualitatively according to the theory used. The theory utilized in this study is the hypothesis of Myers (1992) to recognize the kinds of conflict that happen in the fundamental person, Deetz and Stevenson (1986) to track down ways of managing clashes. Conflict is analyzed based on the literature theory proposed by Kenney (1996), which divides conflict into two types, namely external and internal. However, in the film, only external conflicts occur. External conflicts are emphasized because they drive the plot and highlight the main character’s struggle against outside forces, such as societal pressures, financial hardships, and relationships with other characters.